Evaluation of Protein Carbonyl Content in Healthy and Sick Hospitalized Horses - Nocera, Irene; Bonelli, Francesca; Meucci, Valentina; Rinnovati, Riccardo; Spadari, Alessandro; Intorre, Luigi; Pretti, Carlo; Sgorbini, Micaela (Frontiers in Veterinary Science, 2020)
Literature on the protein carbonyl content (PCC) evaluation in horses is scarce, thus the aims were to evaluate the PCC in healthy and SIRS (Systemic Inflammatory Response Syndrome) horses and to investigate the performances of PCC in terms of sensitivity, specificity and likelihood ratio in identifying SIRS positive and negative horses. A total of 72 adult horses were included. All the horses underwent to a complete physical examination, blood analysis and were evaluated for the SIRS status. Blood samples were collected once in healthy horses and at admission time, then 24, 48, 72 and 96 hours after admission in sick animals. PCC was evaluated using a method previously described. Data were statistically analyzed to verify differences in PCC between healthy vs SIRS positive or SIRS negative horses at all sampling time. The Receiver Operating Characteristic (ROC) curve was performed to verify sensitivity and specificity of PCC in the diagnosis of SIRS-positive and SIRS negative horses. The healthy horses were standardbred mares with a median age of 8.5 years. The sick horses were 31/54 females, 16/54 geldings and 7/54 stallions of different breeds and with a median age of 12 years old. Eight out of 54 sick horses were SIRS negative, while 46/54 were SIRS positive. Statistically significant differences were obtained between healthy and SIRS positive horses, while no differences were observed between healthy and SIRS negative horses at any sampling time. The best cut-off value of PCC to discriminate between SIRS positive, SIRS negative and healthy horses, the sensitivity and specificity of cut-off point, the area under receiver operating characteristic curve, the 95% confidence intervals and the likelihood ratio were reported. We found higher PCC values in sick SIRS-positive horses vs healthy ones with a decrement over time, while no differences at admission, nor during the observational period were obtained in sick but SIRS-negative horses. The value of 0.049 nmol/ml/mg is reported as a potential cut-off for the diagnosis of SIRS positivity vs healthy horses with a sensibility of 74.5% and a specificity of 72.2%. In conclusion, PCC seems to be a sensitive and specific marker for SIRS in horses.